PO-44 - Tissue factor pathway inhibitor-2 (TFPI-2) is cleaved by PRSS3: implication for tumor endothelial cells migration. Issue 140 (April 2016) - Ghilardi, C.; Anastasia, A.; Avigni, R.; Lupi, M.; Giavazzi, R.; Bani, M.R.
Abstract : Introduction: Tissue Factor Pathway Inhibitor-2 (TFPI-2) is a Kunitz-type serine proteinase inhibitor whose expression is up-regulated by VEGF in microvascular and umbilical vein endothelial cells (EC). Despite this, TFPI-2 has been suggested as anti-angiogenic molecule, due to its ability to inhibit the migration/proliferation of EC induced by VEGF. Nothing is known about the precise mechanism of TFPI-2 function tuning in tumor endothelium. Aim: Aim of this study was to investigate the role of TFPI-2 in tumor vasculature, where angiogenesis and vascular remodeling are fundamental for cancer progression. Materials and Methods: Tumor-EC were isolated from ovarian carcinomas and cultured in vitro in presence of factors reproducing the tumor microenvironment (VEGF, FGF-2, EGF). TFPI-2 and PRSS3 silencing was achieved by small interfering RNA (siRNA). Tumor-EC migration was assayed by the wound healing assay. Transcript expression was examined by qRT-PCR. Proteolytic reactions were monitored by western blot. Results: We show that tumor-EC express TFPI-2, the majority of which is released and found anchored in the extracellular matrix. Silencing the expression of TFPI-2 enhances tumor-EC migration, confirming TFPI-2 as an anti-angiogenic molecule. We had previously shown that the cancer vasculature express PRSS3, a trypsin family member able to cleave proteins containing the kunitz-type domains; we reasoned that it could potentially inhibit TFPI-2. Herein, we demonstrate in a cell free system that TFPI-2 directly interacts with and is degraded by active PRSS3. In a more complex biological context, active PRSS3 is able to remove TFPI-2 from the extracellular matrix put down by tumor-EC. Accordingly, silencing PRSS3 causes the extracellular accumulation of TFPI-2 that results in the inhibition of tumor-EC migration. Conclusions: Our results demonstrate for the first time that TFPI-2 is a direct substrate of PRSS3, which hydrolyses TFPI-2 (most likely at the Kunitz-type domains) blocking its anti migratory capability. The proteolytic inactivation of TFPI-2 by PRSS3 might represent a mechanism favoring cancer by increasing angiogenesis and vascular remodeling. Acknowledgement: Supported by the Italian Association for Cancer Research (AIRC).